2015
DOI: 10.2196/jmir.3665
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How the Tobacco Industry Presents and Promotes Itself in Social Media

Abstract: BackgroundThe commercial potential of social media is utilized by tobacco manufacturers and vendors for tobacco promotion online. However, the prevalence and promotional strategies of pro-tobacco content in social media are still not widely understood.ObjectiveThe goal of this study was to reveal what is presented by the tobacco industry, and how it promotes itself, on social media sites.MethodsThe top 70 popular cigarette brands are divided into two groups according to their retail prices: group H (brands wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 16 publications
0
53
0
Order By: Relevance
“…This would better capture relationships which flow from the algorithmic and participatory nature of social media 38. An automated, large-scale analysis of a substantial data set of user interactions among tobacco social media revealed that tobacco-related content grows exponentially while there is linear growth for the tobacco control group 21. In addition, the antitobacco community is more tightly connected, while the much larger protobacco community is sparsely connected.…”
Section: Discussionmentioning
confidence: 99%
“…This would better capture relationships which flow from the algorithmic and participatory nature of social media 38. An automated, large-scale analysis of a substantial data set of user interactions among tobacco social media revealed that tobacco-related content grows exponentially while there is linear growth for the tobacco control group 21. In addition, the antitobacco community is more tightly connected, while the much larger protobacco community is sparsely connected.…”
Section: Discussionmentioning
confidence: 99%
“…A content analysis of UK Top 40 YouTube music videos showed that tobacco imagery appeared in 22% of the videos, and tobacco branding in 4% (Cranwell et al, 2015). A recent comprehensive analysis of the 70 most popular cigarette brands on YouTube revealed over 120,000 pro-tobacco videos (Liang et al, 2015). The YouTube videos focused on the features of tobacco products (79%), information about Web-based shops (49%), and sales promotion (64%).…”
Section: Tobaccomentioning
confidence: 99%
“…Liang and colleagues' comprehensive study of the top 70 popular cigarette brands found that 43 of the brands had created 238 Facebook fan pages, with 1,189,976 page likes and 19,022 posts (Liang et al, 2015). An early study demonstrated that British American Tobacco (BAT) employees were promoting BAT and BAT brands on Facebook by joining and administrating groups, joining pages as fans and posting photographs of BAT events, products and promotional items (Freeman & Chapman, 2010).…”
Section: Tobaccomentioning
confidence: 99%
“…Nevertheless, regulation of online advertising for other substances and preventing underage access has been found to be challenging. Despite banning tobacco advertising on its platform, cigarette brand fan pages were easily found on Facebook (Liang et al, 2015). Furthermore, specific brands of e-cigarettes have been found to advertise on websites with an audience of up to 35% youth (Richardson et al, 2014), and underage Twitter, Instagram, and YouTube users can easily access and interact with alcohol industry content on these platforms (Barry, Bates, et al, 2015; Barry, Johnson, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%